EFFECT OF SINGLE-DOSE PREGABALIN ON POSTOPERATIVE PAIN IN DACRYOCYSTORHINOSTOMY SURGERY: Pregabalin Effect Postdacryocystorhinostomy - Abbas, Sana; Naeem, Saquib; Akram, Amjad; Abbas, Beenish; Iqbal, Rashid (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the analgesic potential of pregabalin in ambulatory dacryocystorhinostomy surgeries under general anaesthesia.Study Design: Quasi-experimental study.Place and Duration of Study: Tertiary Care Hospital Rawalpindi, from Nov 2019 to Sep 2020.Methodology: A total of 110 patients undergoing ambulatory dacryocystorhinostomy surgery at our hospital were included in the study. Participants were divided into two groups, group A (n=55) were administered 150 mg oral pregabalin, while a placebo was given to participants of group B (n=55). Post-operative pain was assessed at recovery, four and eight hours after surgery with the help of the visual analogue scale.Results: Mean age of participants was 43.05 ± 7.5 years. Gender wise distribution showed 62 (56.4%) males and 48 (43.6%) females. At recovery, four and eight hours after surgery the mean pain scores in group A (pregabalin) vs group B (placebo) were (2.98 ± 0.8 vs 4.98 ± 0.8, p